When Biomass Electricity Demand Prompts Thinnings in Southern US Pine Plantations: A Forest Sector Greenhouse Gas Emissions Case Study - Buchholz, Thomas; Gunn, John S.; Sharma, Benktesh (Frontiers in Forests and Global Change, 2021)
Increasing demand for woody biomass-derived electricity in the UK and elsewhere has resulted in a rapidly expanding wood pellet manufacturing industry in the southern US. Since this demand is driven by climate concerns and an objective to lower greenhouse gas (GHG) emissions from the electricity sector, it is crucial to understand the full carbon consequences of wood pellet sourcing, processing, and utilization. We performed a comparative carbon life cycle assessment (LCA) for pellets sourced from three mills in the southern US destined for electricity generation in the UK. The baseline assumptions included GHG emissions of the UK’s 2018 and 2025 target electricity grid mix and feedstock supplied primarily from non-industrial private forest (NIPF) pine plantations augmented with a fraction of sawmill residues. Based on regional expert input, we concluded that forest management practices on the NIPF pine plantations would include timely thinning harvest treatments in the presence of pellet demand. The LCA analysis included landscape carbon stock changes based on USDA Forest Service Forest Vegetation Simulator using current USDA Forest Service Forest Inventory and Analysis data as the starting condition of supply areas in Arkansas, Louisiana and Mississippi. We found that GHG emission parity (i.e., the time when accumulated carbon GHG emissions for the bioenergy scenario equal the baseline scenario) is more than 40 years for pellets produced at each individual pellet mill and for all three pellet mills combined when compared to either the UK’s 2018 electricity grid mix or the UK’s targeted electricity grid mix in 2025. The urgency to mitigate climate change with near-term actions as well as increasing uncertainty with longer-term simulations dictated a focus on the next four decades in the analysis. Even at 50% sawmill residues, GHG emission parity was not reached during the 40 years modeled. Results are most likely conservative since we assume a high share of sawmill residues (ranging from 20% to 50%) and did not include limited hardwood feedstocks as reported in the supply chain which are generally associated with delayed GHG emission parity because of lower growth rates.